Zinc Dynamics in Oil Palm Plants at Different Cultivation Ages - Viégas, Ismael de Jesus Matos; Galvão, Jessivaldo Rodrigues; Ohashi, Alessandra Marie; Coutinho Santos, Mário Davi; da Silva Maia, Bruno Kleidson [UNESP]; Tavares, Victor Hugo; da Costa Pantoja, Matheus Vinicius; Brito, Maria Luiza Brito; Costa dos Santos, Cassio Rafael (Springer Nature, 2025)
The objective of the present study was to determine the concentration and extracted amount of zinc (Zn) in the different components of oil palm plants, based on planting age. The research was conducted in the experimental field of Agropalma Sociedade Anônima, in the municipality of Tailândia, PA, Brazil, using a completely randomized design with four replications. We collected the leaflets, petioles, rachis, palm heart, arrows, stem, male inflorescences, peduncles, spikelets as well as fruits. The stipe had a greater capacity to store Zn (77%), than the leaflets (11%). The participation of fruits in exports ranged from 56.5 to 88.6% and in spikelets, it ranged from 8.3 to 37.4%, while in peduncles, it was 3.1–7.9%, respectively. The extracted Zn corresponded to 1753.98 g ha-1. The amount fixed in the eighth year was 8.4 times and the recycled amount was 1.3 times greater than the exported quantity. The petiole was the most efficient component in Zn usage. The highest total efficiency was obtained in the 8th year of cultivation. The age of plants influences the accumulated amount of Zn in plant components, highlighting a greater nutritional requirement throughout age and production periods. Therefore, oil palm can reuse Zn in new vegetative tissues over time, even without fertilization, because it accumulates this nutrient in mature organs, which denotes the need for adoption of management practices that favor this Zn reranslocation and reuse in oil palm plantations.
Keywords: Arecaceae; Elaeis guineensis; Jacq; Micronutrients; Mineral nutrition; Nutrients use efficiency